Nongastrointestinal Symptoms of Irritable Bowel Syndrome: An Office-Based Clinical Survey - NB Hershfield (Canadian Journal of Gastroenterology)
Irritable bowel syndrome (IBS) is the most prevalent gastrointestinal problem faced by practicing gastroenterologists. For many years, nongastrointestinal symptoms have been documented in IBS patients, but the medical literature does not emphasize them. The present study explored how IBS and inflammatory bowel disease patients differ in their reporting of nongastrointestinal symptoms. Information from 200 consecutive patients with IBS and a similar number of patients with Crohn's disease (in a single gastroenterology practice) was obtained at the initial visit using a simple questionnaire. Comparison of the data revealed that IBS patients describe certain nongastrointestinal symptoms far more frequently than do those with inflammatory bowel disease. It is recommended that these symptoms be considered along with the generally accepted criteria for making a positive diagnosis of IBS.